Abu Eisa At-Tirmidhi and The Science Of Jarh and Ta’dil - Bakhriddinovich, Abdusattarov Ilhom (Indonesian Journal Publisher, 2024)
This article points out jarh and ta’dil, which are the most important sciences in hadith studies, as well Abu Eisa at-Tirmidhi and his method of examining hadith narrators, his views on “jarh and ta’dil”, and also his teachers in the science of narration. The science of “jarh and ta’dil” discusses the verification of the narrators of hadiths and reports in order to distinguish the acceptable hadith from the rejected ones, and defines reliable hadiths from the weak and matruk ones.